Higher Education Language Translation Practices in North Sumatra: Case Study of Lecturer and Student Perceptions - Manik, Kresna Ningsih; Sai Davis, Yong Heng; Nababan, Irene Adryani; Agus Salim Marpaung; Masitowarni Siregar; T. Silvana Sinar (CV. AFDIFAL MAJU BERKAH, 2024)
This research explores the multifaceted concept of translanguaging in the context of teaching English as a foreign language in three universities in North Sumatra. Translanguaging, a term encompassing various aspects of multilingualism, is examined as a pedagogical approach that utilizes multiple languages within a classroom setting. The study investigates translanguaging practices among lecturers and aims to address three key research questions: the types of translanguaging practices, perceptions of lecturers and students, and the motivations behind incorporating translanguaging in teaching and learning activities. The research method is a qualitative method with a case study approach model focusing on the exploration of a